Influence of center-based child care on development of two-year-olds in a Brazilian cohort - Leão, Otávio Amaral de Andrade; Mielke, Gregore Iven; Silveira, Mariângela Freitas da; Domingues, Marlos Rodrigues; Murray, Joseph; Neumann, Nelson Arns; Dalabona, Caroline Caus; Bertoldi, Andréa Dâmaso (Revista de Saúde Pública, 2021)
OBJECTIVE To investigate the association between child care attendance since birth and development in two-years-old Brazilian children. METHODS The study used longitudinal data from the 2015 Pelotas Birth Cohort. The childhood development (cognitive, fine and gross motor skills, and language) at two-years-old children was assessed using INTER-NDA (INTERGROWTH-21st Neurodevelopment Assessment). The child care attendance was measured at ages one and two years and categorized as: a) never attended child care; b) attended some child care (one or two years); and c) always attended child care (one and two years). Demographic, socioeconomic, health, and child stimulation variables were considered as confounders. Crude and adjusted analyses of child care attendance and development were carried out using linear regression. RESULTS Out of the 3,870 infants included in the analyses, around 1/3 attended center-based child care. In crude analyses, attending center-based child care was associated with positive developmental outcomes, except in motor domains. In adjusted analyses, compared to those children that have never attended child care, children who did attend presented higher scores for cognitive development (always in child care: β: 2.44, 95%CI: 0.83–4.05; some child care: β: 1.35, 95%CI: 0.17–2.53). CONCLUSIONS This study suggests that center-based child care may help improve child cognitive development in the Brazilian context. Furthermore, the association was higher for early and continued attendance. Considering the low prevalence of children in external care, it is recommended to improve child care opportunities in early childhood.